Desacralization in Dressing as a Political Identity for World Peace in the Millennial Era - Hayati, Shohwunni (International Journal Ihya' 'Ulum al-Din, 2020)
When someone dress, other people easily judges about the culture or religion that others have. It invites differences of opinion in enforcing rules within an institution such as schools, campuses, and offices. On March 06, 2018 BBC News reported there was a ban on wearing the face mask (cadar) at a state Islamic university because the threat of radicalism which always gave birth to new people especially in the millennial era now.This is because for some people the face mask (cadar) is seen as a sign of the development of conservative Islam and shows one's identity. But it creates public unrest and some people feel uneasy about the sacralization in the dress. Researcher used library research methods by using descriptive-qualitative type by using primary sources, literature on the theory of desacralization and politic of identity and secondary sources is from several supporting literature. The results, desacralization in dressing is that a person does not contain sacred in clothes except when worship this is at a profane time that dressing has a good meaning with applicable state regulations. Desacralization in dress as politics of identity will be able to position his own identity without disturbing the identity of others.